SERUM PROTEIN AND ALBUMIN, LIPID AND CHOLESTEROL CONCENTRATION IN NORMAL ADULT POPULATION OF DISTRICT ABBOTTABAD - Khan, Mir Hassan; Khan, Jahangir A.; ullah, Rizwan (Journal of Ayub Medical College Abbottabad, 1989)
Abstract: Serum Protein and albumin, lipid and cholesterol levels were studied in 200 randomly selected apparently healthy subjects (118 males and 82 females) of different ages. Age range was between 20-70 years. No significant difference was observed in total protein and albumin levels in both sexes of various age groups. Lipid pattern was positively correlated with the age in males however, in females, this pattern was decreased after 50 years’ age. Cholesterol showed a progressive rise in both sexes between the ages 20-49 years after which begin to fall. Results also showed Lipid and Cholesterol levels were lower in the females compared to age matched males.